Dielectric properties and electrical conductivity of FeGa0.8In1.2Se4 crystals on alternating current - Niftiyev, Namiq; Mammadov, Faik; Azizova, Asmet; Hashimov, Khanlar; Babanly, Mahammad (Physics and Chemistry of Solid State, 2026)
Dielectric permeability and electrical conductivity of FeGa0.8In1.2Se4 crystal at different frequencies and temperatures were studied. It was determined that the real and imaginary parts of the dielectric permittivity were subjected to a significant degree of dispersion, which has the character of relaxation. In this crystal, the regularity σ ~ fS (0.1≤ S ≤ 1.0) is satisfied for electrical conductivity in the temperature range 295 ÷ 358 K and the frequency range 2·104 ÷ 106 Hz and it is assumed that there is a hopping conduction mechanism. The activation energy of charge carriers for the FeGa0.8In1.2Se4 crystal was determined.